Tutela coletiva dos interesses individuais homogêneos - Branco, José Eduardo (2008)
The present work has the target of analyzing the procedural subjects involving the guardianship of homogeneous individual interests, while species of the gender of the interests or collective rights. From the doctrinary and jurisprudential analysis, it looks for the ideal understanding of the legal concepts that involve the studied theme, as well as the systematization of the collective guardianship and its harmonization with the general principles that govern our legal system. Without the pretension of exhausting the lifted up subjects, in reason of the present time of the theme, still unification pendant by the legislative way, and while the text promulgation is awaited that ponders all the kindred institutes, it accomplishes doctrinary research with the purpose of bringing current conclusions concerning the matter and the legal dispositions that today regulate the guardianship of collective interests. In this manner, subjects as the active legitimacy, the judged thing and its reach, the systemic interaction and the procedures to be used to reach the leading principles of the collective guardianship, above all by the way of the homogeneous individual interests, are analyzed through the points that cause larger controversies for, since then, to understand that new procedural reality. In that line, of great relief are the lessons of our doctrine, that from a long time develops studies seeking to adapt the existent procedural legislation and its traditional institutes to the new rights that were born with the mass society and started to demand more effective solutions for the great number of judicial demands that flow of the modern world. The Social State delineated by the Constitution of 1988 could not take place under foundations created exclusively for a law worried, above all, with the individual subjects, unable even of assisting to the democratic vindications of the contemporary society, reason for the law science, through the performance of combative and dedicated legal scholars, needed to present that new system of procedural guardianship of rights. The relevance of the collective guardianship of homogeneous individual interests and the created techniques for that are, therefore, the main point of the present study, that looks for in the doctrinary lessons the foundation to demonstrate the adaptation of the existent legal devices to that guardianship, considering for that the jurisdictional performance and the legislative projects now in course